Pathophysiology and burden of infection in patients with diabetes mellitus and peripheral vascular disease: focus on skin and soft-tissue infections. (1st September 2015) - Dryden, M.; Baguneid, M.; Eckmann, C.; Corman, S.; Stephens, J.; Solem, C.; Li, J.; Charbonneau, C.; Baillon-Plot, N.; Haider, S.
Abstract: Diabetes mellitus affects 284 million adults worldwide and is increasing in prevalence. Accelerated atherosclerosis in patients with diabetes mellitus contributes an increased risk of developing cardiovascular diseases including peripheral vascular disease (PVD). Immune dysfunction, diabetic neuropathy and poor circulation in patients with diabetes mellitus, especially those with PVD, place these patients at high risk for many types of typical and atypical infections. Complicated skin and soft-tissue infections (cSSTIs) are of particular concern because skin breakdown in patients with advanced diabetes mellitus and PVD provides a portal of entry for bacteria. Patients with diabetes mellitus are more likely to be hospitalized with cSSTIs and to experience related complications than patients without diabetes mellitus. Patients with PVD requiring lower extremity bypass are also at high risk of surgical site and graft infections. Methicillin-resistant Staphylococcus aureus (MRSA) is a frequent causative pathogen in cSSTIs, and may be a significant contributor to surgical site infections, especially in patients who are colonized with MRSA on hospital admission. Patients with cSSTIs and diabetes mellitus or PVD experience lower clinical success rates than patients without these comorbidities, and may also have a longer length of hospital stay and higher risk of adverse drug events. Clinicians should be vigilant in recognizing the potential for infection with multi-drug-resistant organisms, especially MRSA, in these populations and initiating therapy with appropriate antibiotics.